Disposição construtiva aplicada em ponto/parada de ônibus: uma abordagem para melhorar o conforto dos usuários aproveitando as tecnologias nas cidades - CAMARA, Andreia Jane Leandro (2023)
The present work deals with the constructive disposition applied in a bus stop, based on the minimum and desirable requirements in its physical installations. This study consists of giving these small constructions an identity with large supports inserted in the local context, linked to the urban functions of public spaces. In this scenario, this work aims to develop a constructive arrangement aimed at the structural and functional optimization of a bus stop based on the combination of patentable technological solutions. The research used the descriptive exploratory approach method, developed with indirect documentation and bibliographical research, in the CAPES Periódicos portal, survey of trends in the world scenario of technologies in the scope of patents aimed at bus stops carried out in the patent bases: USPTO, EPO and INPI. Construction of a prototype (electronic model) of the bus stop using AutoCAD 2023 and SketchUp software and writing of the invention patent. The results showed that the number of patents found is higher on the USPTO platform, followed by the EPO and then the INPI. The small number of patents found at the INPI with this theme and the few technological solutions presented enabled the construction of a prototype (electronic model) of the bus stop that consists of a combination of patentable technological solutions with multifunctionalities that together offer connectivity and accessibility, which led to the writing of an invention patent entitled: “Constructive disposition applied at a bus stop/stop” and its filing with the INPI. It is concluded that the generated product can be applied and replicated in the form of modules in municipalities nationwide, and may be of interest to city halls and state departments as well as private companies.